Ethnobotanical study of medicinal plants traditionally used against erectile dysfunction in Tabora region, Tanzania - Kacholi, David Sylvester; Amir, Halima Mvungi (Ethnobotany Research and Applications, 2023)
Background: Globally, erectile dysfunction (ED) is a public health concern that upsets men's psychosocial well-being. Despite using indigenous knowledge to manage various disorders in Tanzania, there is a lack of data on the medicinal plants (MPs) used to manage ED. Therefore, this study was aimed at documenting MPs traditionally used by traditional healers (THs) to manage ED in Tabora region, Tanzania. Methods: An ethnobotanical survey was conducted from June to October 2020. A semi-structured questionnaire was used to collect information from 38 THs in 9 wards, explicitly asking about MPs used against ED, parts used, methods of preparation, and routes of administration. The collected information was analyzed by computing percentage frequencies and familiarity index. Results: Thirty-four plant species belonging to 21 families and 32 genera were documented to be used to manage ED. Family Fabaceae (26%) dominated the species used in the treatments. Abrus precatorius L. (59%), Senegalia senegal (L.) Wild., Ricinus communis L. (with 57% each), Coffea arabica L., and Flueggea virosa (Willd.) Voigt. (56% each) were the most cited MPs. Tree (52%) and root (60%) were the most utilized growth form and plant part, respectively. Decoction (34%) and oral (97%) were the most used methods of preparing and administering the remedies, respectively. Conclusion: The findings indicate that the region has diverse MPs for treating ED. Most MPs used by THs to treat ED are yet to be tested; thus, further research is required to authenticate the efficacy of the herbal remedies and to formulate low-cost contemporary drugs. Keywords: Ethnomedicine, herbal remedies, impotence, Traditional medicine, Tanzania